Effects on Glomus mosseae Root Colonization by Paenibacillus polymyxa and Paenibacillus brasilensis Strains as Related to Soil P-Availability in Winter Wheat - Veronica Arthurson; Karin Hjort; Diriba Muleta; Lotta Jäderlund; Ulf Granhall (Applied and Environmental Soil Science)
Greenhouse experiments were conducted to assess the effects of inoculating winter wheat (Triticum aestivum) with plant growth promoting rhizobacteria (PGPR) of the genus Paenibacillus under phosphate P-limited soil conditions in the presence or absence of the arbuscular mycorrhizal fungus (AMF) Glomus mosseae. Four P. polymyxa strains and one P. brasilensis strain were compared at two cell concentrations (106 and 108 cells g−1 seeds) of inoculation, and surface sterilized AMF spores were added to pots. Mycorrhizal root colonization, plant growth, and plant uptake of phosphorus were analyzed. Bacterial phosphate solubilization was examined separately in vitro. Most P. polymyxa strains, isolated from wheat, had dramatic effects per se on root growth and root P-content. No treatment gave significant effect on shoot growth. AMF root colonization levels and total plant uptake of P were much stimulated by the addition of most P. polymyxa strains. The AM fungus alone and the P. brasilensis, alone or in combination with the fungus, did not affect total plant P-levels. Our results indicate that practical application of inoculation with plant host-specific rhizobacteria (i.e., P. polymyxa) could positively influence uptake of phosphorus in P-deficient soils by wheat plants, provided that suitable AM fungi (e.g., G. mosseae) are present.